2020
DOI: 10.1073/pnas.2001284117
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of sitting behavior at work

Abstract: Sitting for prolonged periods of time impairs people’s health. Prior research has mainly investigated sitting behavior on an aggregate level, for example, by analyzing total sitting time per day. By contrast, taking a dynamic approach, here we conceptualize sitting behavior as a continuous chain of sit-to-stand and stand-to-sit transitions. We use multilevel time-to-event analysis to analyze the timing of these transitions. We analyze ∼30,000 objectively measured posture transitions from 156 people dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Numerous examples of sudden gains and losses in complex systems exist in the literature, from asthma attacks [ 25 ], shifts in motivational flow [ 26 ], improvements or aggravations of symptoms in individuals with depression, mood and/or anxiety disorders [ 27 ], and, at a broader level, forms of societal collapse [ 28 ] or climatic change [ 29 ]. In the health behavioral science literature, recent studies found that sleep stage transitions [ 30 ], as well as sedentary behaviors (i.e., time spent sitting) [ 31 ], were characterized by such irregular patterns of change. More volitional behaviors, such as daily changes in alcohol consumption, have also been successfully modelled with methods allowing the consideration of non-linearity and non-stationarity [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples of sudden gains and losses in complex systems exist in the literature, from asthma attacks [ 25 ], shifts in motivational flow [ 26 ], improvements or aggravations of symptoms in individuals with depression, mood and/or anxiety disorders [ 27 ], and, at a broader level, forms of societal collapse [ 28 ] or climatic change [ 29 ]. In the health behavioral science literature, recent studies found that sleep stage transitions [ 30 ], as well as sedentary behaviors (i.e., time spent sitting) [ 31 ], were characterized by such irregular patterns of change. More volitional behaviors, such as daily changes in alcohol consumption, have also been successfully modelled with methods allowing the consideration of non-linearity and non-stationarity [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, what psychological processes (e.g., related to effort, reward, affect, and fatigue) are associated with healthy and unhealthy sedentary behavior? Answering this question will pave the way for the development of novel, targeted interventions that will improve (occupational) health [ 155 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to another computer-based e-health intervention [ 49 ], the manual entry required to log a break via the application was also commonly perceived as clunky and inconvenient, and there were calls from participants to map the smartphone technology to inbuilt accelerometer capabilities to automatically detect when a person had broken up their sedentary time; link with existing wearable technologies such as a wrist worn device; or sync with participants workday calendar/schedule to tailor the intervention strategy and detect when participants were in meetings and avoid prompts at inconvenient or inappropriate times. While tailoring future strategies to individual needs seems important, a cross sectional study among predominately desk-based workers also showed that employees are naturally quicker at transitioning between seated and standing postures later on in the working day [ 50 ]. Considering the temporal dynamics of SB within workplace in addition to the method and frequency of prompt delivery may also help to optimize compliance and behavior change and increase acceptability and feasibility over time.…”
Section: Discussionmentioning
confidence: 99%